2022
DOI: 10.17657/jcr.2022.7.31.4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Consumer Evaluation of ESG for Food Subscription Services on Intention to Word-of-Mouth and Continuous Usage: Moderating Role of Altruism

Abstract: consumers' ESG evaluation, the more positive the word of mouth intention and the intention to continue using it.Second, governance (G) had a positive (+) effect on word of mouth intention, but rejected the positive (+) relationship with continued use intention. Third, as for the moderating effect according to altruism, the higher the altruism, the higher the environmental (E) and social (S) dimensions positively adjusted word-of-mouth intention and continued use intention. Also, the relationship between govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Similarly, Park [49] identified the influence of the suitability of CSR activities and business contents of companies on attitudes toward companies and WOM intentions based on the persuasion knowledge model. In addition, Kim, Jeong, & Park [50] evaluated the ESG activities of companies. They found that among the elements of ESG, the more positive the evaluation of environment (E) and society (S), the more positive the effect on WOM and continued use intention among people who experienced regular food delivery through a subscription service.…”
Section: Word Of Mouthmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Park [49] identified the influence of the suitability of CSR activities and business contents of companies on attitudes toward companies and WOM intentions based on the persuasion knowledge model. In addition, Kim, Jeong, & Park [50] evaluated the ESG activities of companies. They found that among the elements of ESG, the more positive the evaluation of environment (E) and society (S), the more positive the effect on WOM and continued use intention among people who experienced regular food delivery through a subscription service.…”
Section: Word Of Mouthmentioning
confidence: 99%
“…In Section 3, the estimation of brand trust adapts and modifies three items from Dywer et al [24] and Krishnan [30]. In Section 4, WOM is measured based on Court, Elzinga, Mulder, & Vetvik [57] and Kim et al [50]. The final section of the questionnaire accesses relevant demographic information of survey participants.…”
Section: Measurement Itemsmentioning
confidence: 99%